KEAWETAN 99 JENIS KAYU INDONESIA TERHADAP RAYAP KAYU KERING - Ginuk Sumarni; Han Roliadi; Agus Ismanto (Pusat Penelitian dan Pengembangan Hasil Hutan, 2003)
The resistance of 99 Indonesian wood species against dry wood termite (Cryptotermes cynocephalus Light) attack has been assessed. The wood species come from several regions in Indonesia. The woods were each cut to small samples measuring 5.0 cm by 2.5 cm by 2.0 cm and subsequently exposed to 50 dry wood termite of workers for twelve weeks.The results revealed that out of the 99 investigated wood species 33 (i.e. 33.33%) were classified as the most durable wood (classes I and II); and the rest, i.e. 66 species (66.6 %), were classified was lower durability (i.e. classes III, IV, and V) and, therefore, in their utilization, a preservative treatment is required.